The development of textile industry in Shtip - Zhezhova Silvana; Jordeva Sonja; Golomeova-Longurova Sashka; Maksimov Stefan; Dimitrijeva-Kuzmanoska Vanga (Tekstilna industrija, 2021)
The city of Shtip is the main garment production center in the Eastern part of the Republic of North Macedonia. The textile industry participates with 70% in the total achievements of the industry in the Municipality. There are over 60 companies for production of clothes in Shtip, and among their most important partners are Germany, Italy, Austria, Belgium and the Netherlands. Most of the clothing companies are organized as small or medium enterprises for production of casual clothes such as shirts, blouses, etc., which operate on the basis of the "LON" (LOHN) production system.